Growth And Yield of Onion (Allium ascalonicum L.) Against Various Concentrations of Liquid Organic Fertilizer - Sri Lestari Galagi; Aiyen Aiyen; Muhammad Anshar Pasiga (AGROLAND The Agricultural Sciences Journal (e-Journal), 2017)
Onion (Allium ascolanicum L.) is not only popular as cooking spices in Indonesia but also throughout the world. Onion that has high economic value, has its own attraction to be cultivated by farmers. However, farmers often face some problems in onion farming. Problems were faced by farmers related to social economic conditions both internal, external and natural conditions. Fertilizer application for onion can use inorganic and organic fertilizer materials. The use of inorganic fertilizers without the addition of organic fertilizers over a long period of time, suspected to cause a decrease in soil physical and chemical capabilities, with the application of solid and liquid organic fertilizer is predicted to be more effective because the elements are more than one element. The use of fertilizers and organic matter through soil is often inefficient because of the fixation by soil particles. Liquid fertilizers administered overcome gapnutrients during growth. Herbafarm liquid organic fertilizer is a type of liquid fertilizer released by PT. Sidomuncul herbafarm which contains bio protectant, processed from by products of medicinal products made from raw medicinal plants and spices. Herbafarm contains macro and micro nutrients and also organic compounds that are essential for the growth and development of plants. This research was conducted in Sidera village, Biromaru sub-district, Sigi regency, Central Sulawesi Province. This study used a Randomized Block Design consisting of 5 treatment levels: P0 = control, P1 = 1 ml/liter of water, P2 = 2 ml/Liter of water, P3 = 3 ml/liter of water, and P4 = 4 ml/liter of water. All treatments were repeated 4 (four) times, so that there were 5 treatments each time 4 replicates = 20 experimental units. The results of this research were the best herbafarm POC on the treatment of 4 ml/liter of water that was on the parameters of plant height of 33,56 cm, leaves number as much as 30. 63 blades, total dry weight of crop 9.99 g, number of tubers per family of 8.13 fruit, tuber diameter of 20.26 mm, tuber length of 34.55 mm, fresh tuber weight per family of 32.57 g, tuber water content of 114.54 g and Weight of tuber per hectare 8.68 ton.ha-1.